Legal Compliance in Street‐Level Bureaucracy: A Study of UK Housing Officers. (3rd December 2015) - Hunter, Caroline; Bretherton, Joanne; Halliday, Simon; Johnsen, Sarah
Abstract : Street‐level bureaucratic theory is now at a fairly mature stage. The focus on street‐level bureaucrats as ultimate policymakers is now as familiar as it is important. Likewise, the parallel sociolegal study of the implementation of public law in public organizations has demonstrated the inevitable gap between law‐in‐the‐books and law‐in‐action. Yet, the success of these advances comes at the potential cost of us losing sight of the importance of law itself. This article analyzes some empirical data on the decision making about one legal concept— vulnerability in UK homelessness law. Our analysis offers two main contributions. First, we argue that, when it comes to the implementation of law, the legal abilities and propensities of the bureaucrats must be taken into account. Bureaucrats' abilities to understand legal materials make a difference to the likelihood of legal compliance. Second, we must also pay attention to the character of the legal provisions. Where a provision is simple, it is more likely to facilitate legal knowledge and demands nothing of bureaucrats in terms of legal competence. Where the provision is also inoffensive and liveable, it is less likely to act as an impediment to legal conscientiousness.